PEMAHAMAN KONSEP SPLDV PESERTA DIDIK KELAS VIII SMP 10 NOPEMBER JAKARTA - Auliya, Farah Dita; Suhendri, Huri; Setiadi, Asep (Pendidikan Matematika FMIPA Universitas PGRI Banyuwangi, 2024)
This research aims to describe the understanding of mathematical concepts of class VIII students at SMP 10 November Jakarta in the material Systems of Linear Equations in Two Variables (SPLDV). This research is a mix-method type or combined research (quantitative-qualitative). The respondents were 28 students in class VIII-B, and 1 mathematics teacher as informant. Data collection was carried out using test and interview techniques. The results show that class VIII-B students’ understanding of the SPLDV concept is still relatively low. Indicators of concept understanding that has not been achieved optimally are: classifying objects according to certain properties in accordance with concept, presenting concepts in various forms of mathematical representation, and developing necessary and sufficient conditions for a concept. The failure to understand this concept is due to students’ lack of focus in the learning process and efforts can be made to improve this by asking students to repeat learning at home.